THE MORE COMMON LESIONS AT SOCCER, FUTSAL, BASKETBALL, VOLLEYBALL AND ITS BIOMECHANIC CORRELATIONS FOUND IN THE ATHLETES OF SPORTS MUNICIPAL CENTERS OF JACAREZINHO-PARANÁ (Fiep Bulletin - online, 2014)
The prevention programs may help the sports practice to enhance their benefits to the athletes' health and minimize the lesions occurrence. (ELLENBECKER, 1992; WILK et al, 1993). OBJECTIVE: Compare the most common lesions to the biomechanics of the practiced modalities by the athletes taking into consideration the maturation, growing, training time. METHODOLOGY: A questionnaire and a physiotherapeutic evaluation were applied to 176 athletes within the modalities of male and female futsal and basketball, male soccer and female volleyball of the Sports Municipal Centers of Jacarezinho. They verified the berlis@visaonet.com.br 261 FIEP BULLETIN Volume 78 - Special Edition - ARTICLE I - 2008 related lesions by the athletes at clinic anamnese, comparing the averages with the biomechanics of each modality. The sample was considered homogeny analyzing averages and standard deviations male and female respectively: male 131 athletes: age 13 (2), height 158 cm (15), weight 37 kg (9), and training period of 20,5 months (13); female 45 athletes: age 13 (2), height 152 cm (7), weight 49 kg (8), and training period 19,4 months (23). RESULTS: 68% of the athletes had lesions. These lesions: Male futsal, 36% knee and 37% lumbar column; Male soccer, 50% lumbar column and 40% knee; Male basketball, 40% knee and 33% ankle; Female futsal, 37% knee and 25% lumbar column; Female volleyball, 24% breast column and 24% knee; Female basketball, 37% ankle and 25% wrist. CONCLUSION: The found lesions at each sport can be compared to biomechanics and its specification, inasmuch as they can be enhanced by the postural alterations made clear through the period of maturation, growing, and athletes' postural habits assessed. These data may be the base for a Preventive Physiotherapeutic Program improving the quality of life and production of the young athletes.
Keywords: sportive physiotherapy; biomechanics; lesion